Poverty and Inequality (London : C. W. Publishing Ltd.)
1944-10 1944 1940s 29 pages 22 the claimant will get nothing. Employers are not obliged to insure against this risk. (5) In point of fact, most large employers do insure ; but this has its own evils. It transfers the employers' responsibility to the big insurance companies, who are not in the least interested in the welfare of the worker, but only in their own profits. The unfortunate little man finds himself in opposition to all the resources of these powerful organisations. Their experts are quick to note where a claim can be avoided by a legal quibble ; their agents, by dazzling him with the offer of a lump sum which is less than his due, know how to persuade the injured man not to seek his rights in court. (6) If he does take the matter to court he runs a far greater risk than his rich opponent, for if he loses, he loses everything. Free legal aid in civil cases can be granted only to persons not earning more than £2 per week and not "worth" more than £50. In exceptional cases the figures are £4 and £100 respectively. An initial deposit of between £3 and £10 is required. Thus a single man earning £4 a week may receive assistance, but a married man with four children earning £4 5s. cannot. Moreover, assistance is only given in respect of High Court proceedings ; there is no help whatever for poor litigants in the County Court, and the loser of an action in it may have to pay from £20 to £50 costs. Yet this is "the poor man's court," for here all cases (except divorce) which involve a sum of £100 or less are heard. (7) War Pensions. War Pensions have been extended during this war to cover the entire population in the event of war injury (as a direct result of enemy action or of combating the enemy) or of war service injury (incurred in the course of military or civil defence duties). They are not, of course, in all cases, a measure for the relief of poverty, since they are paid to rich and poor alike. War Pensions were increased in August, 1943, but are still far below the rates paid by the Dominions. The ranks are paid at a much lower rate than officers. A totally disabled British private, for example, receives £104 a year. A subaltern gets £210. Anyone over the rank of Major-General gets £420. The rates are the same for corresponding ranks in other services. Civilian rates are the same as for the lowest rank of the armed forces. The inequality in Service Pensions is defended on the ground that it merely reflects the inequality of remuneration between the social classes in civilian life. The pensions of privates and N.C.O.'s should at least be stepped up to the amount received by a lieutenant, as they are in Canada. Children's allowances normally terminate at 18 for the children of officers, but at 16 for other ranks, unless the applicant 15X/2/98/13